2021
DOI: 10.4103/jhrs.jhrs_191_20
|View full text |Cite
|
Sign up to set email alerts
|

Serum Irisin Levels and its Association with Blood Glucose and Insulin Indices in Diagnosing Insulin Resistance in Adolescents with Polycystic Ovarian Syndrome

Abstract: Context: Irisin, a new myokine, has been found to be a biological marker of insulin resistance (IR). There is conflicting evidence on serum irisin level in adult women with polycystic ovarian syndrome (PCOS), and data are lacking in adolescents with PCOS. Aims: We aimed to evaluate serum Irisin levels and study its association with indices using blood glucose and insulin levels in adolescents with PCOS. Settings and Design: This case–control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Among the reproductive hormones only progesterone and testosterone showed significantly correlated with irisin level innonobese PCOS and obesePCOSpatients respectively. Similar observation was also reported previously however physiological interpretation of the relation yet to be evaluated 9 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Among the reproductive hormones only progesterone and testosterone showed significantly correlated with irisin level innonobese PCOS and obesePCOSpatients respectively. Similar observation was also reported previously however physiological interpretation of the relation yet to be evaluated 9 .…”
Section: Discussionsupporting
confidence: 89%
“…In our study we observed expectedly ovarian hormonal level (testosteronestrogen, progestron)were decreased whileLH/FSH)ratio were increasedin PCOS compared to corresponding healthy control as described before 9,18 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Since insulin resistance plays a major role in pathogenesis of PCOS,[ 2 ] serum irisin could serve as a marker of IR. [ 27 ] Studies have been conducted with metformin for any change in irisin and HOMA-IR in PCOS cases. [ 11 21 ] The present study showed a significant decrease in serum irisin levels in the MF group compared to the LSM group.…”
Section: Discussionmentioning
confidence: 99%